WEB – ТЕХНОЛОГИЯЛАР АСОСИДА БЎЛАЖАК ИНФОРМАТИКА ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ КОМПЕТЕНТЛИГИНИ ШАКЛЛАНТИРИШНИНГ НАЗАРИЙ АСОСЛАРИ - Мамбетниязов, М.Т. (SCIENCE and SOCIETY, 2021)
The article reflects the theoretical foundations of the professional competence of a future computer science teacher on the basis of Web technologies and the study of problems in this area.
Keywords: professional competence; computer science teachers; computer; information; Internet; Web-technology; modern education system